The S in Corporate Social Responsibility and Performance of the US Telecommunications Industry - Kweh Q.L.; Lu W.-M.; Azizan N.A.; Wang W.-K. (John Wiley and Sons Ltd, 2023)
This paper examines the relationship between corporate social responsibility (CSR) and corporate performance. Using a two-stage approach, we first evaluate the efficiency and metafrontier framework of companies in the US telecommunications industry. In the second stage, we run ordinary least squares regression analysis to examine the relationship between CSR and corporate performance. Our first-stage findings show that the sample companies should first improve their scale inefficiencies rather than the inefficiencies in management practices. Through analysis on metatechnology ratios, we provide an insight on the potential improvement in performance caused by changes in the production environment. Our second-stage analysis shows that the social aspects of CSR have positive impacts on corporate performance. Overall, this study contributes to increased understanding of the social aspects of CSR and the performance of US telecommunications companies. © 2014 John Wiley & Sons, Ltd.